Empirical Relationships between Banana Yields and Climate Variability over Uganda - Sabiiti, Geoffrey; Ininda, Joseph Mwalichi; Ogallo, Laban; Opijah, Franklin; Nimusiima, Alex; Otieno, George; Ddumba, Saul Daniel; Nanteza, Jamiat; Basalirwa, Charles (J. Environ. Agric. Sci, 2016)
Variations in weather and climate have a significant impact on rain-fed banana yields in East Africa. This study examined empirical linkages between banana yields and variations in rainfalland temperature over Uganda for the historical period (1971-2009) using time series moments,correlation and regression analysis. The Food and Agriculture Organization (FAO) Crop Water Assessment Tool (CROPWAT) was used to estimate banana crop water requirements, soil moisturedeficits and their effects onbanana yield levels under rain-fed conditions for different regions. Thestudy observed high comparability in moment indices with some significant differences reflected in thevalues of the banana yields and rainfall and temperature moment indices. The cumulative effect ofrainfall and temperature variations on banana yields was discernible from strong correlationcoefficients of up to 78%. The CROPWAT simulations indicated up to 46% reductions in optimalbanana yields due to soil moisture deficits within banana plantations. In conclusion, the study observedstronger linkages between banana yields and temperature variations than rainfall. In addition,temperature manifests both direct and indirect effects on banana growth while rainfall exhibitscomparatively high intra-seasonal and intra-annual variability with lag effects on banana yields. Thestudy provides a strong scientific basis for the development of coping, adaptation and mitigationstrategies in the banana farming subsector in the region due to the anticipated shifts in rainfall and temperature extremes and changes across Uganda and neighbouring regions.
Keywords: Empirical linkages; Rainfall; Temperature; Soil moisture; Banana yields